Human umbilical cord mesenchymal stem cell-derived microvesicles alleviate pulmonary fibrosis by inhibiting monocyte‒macrophage migration through ERK1/2 signaling-mediated suppression of CCL2 expression - Xiuping Liang; Yanhong Li; Yinlan Wu; Tong Wu; Deying Huang; Ziyi Tang; Lu Cheng; Chunyu Tan; Ronghui Liao; Jing Zhao; Zehui Liao; Yubin Luo; et al. (Stem Cell Research & Therapy)
Abstract Background Pulmonary fibrosis (PF) is a disease with high morbidity and mortality rates, but effective treatment options are extremely limited. Mesenchymal stem cells (MSCs) and their derivatives show promise as potential therapeutics for PF. However, the underlying mechanisms responsible for these beneficial effects remain poorly understood. The objective of this study was to elucidate the specific mechanism through which microvesicles derived from human umbilical cord MSCs (MSC-MVs) alleviate PF. Methods The effects of MSC-MVs on PF in bleomycin (BLM)-induced mice were assessed via histological staining, flow cytometry, and enzyme-linked immunosorbent assays (ELISAs). The potential therapeutic target was identified via RNA sequencing (RNA-seq) analysis, followed by validation via real-time quantitative polymerase chain reaction (RT‒qPCR), ELISAs, scratch testing, and western blotting (WB). Results MSC-MVs significantly attenuated collagen fiber deposition and downregulated the expression of extracellular matrix components in the lungs of the BLM-induced mice. Moreover, this treatment substantially ameliorated lung inflammation by reducing the monocyte‒macrophage ratio and the TNF-α and IL-6 levels. Further analyses revealed that MSC-MVs inhibited the classic chemotactic CCL2/CCR2 axis of monocyte‒macrophages, leading to reduced recruitment of monocytes‒macrophages to the lungs, which decreased lung inflammation and prevented fibrotic progression. Both in vitro and in vivo findings demonstrated that MSC-MVs suppressed ERK1/2 phosphorylation followed by decreased CCL2 production to modulate monocyte–macrophage migration. Conclusions Our findings demonstrate that the protective effect of MSC-MVs against BLM-induced lung toxicity was achieved through the inhibition of the ERK1/2 signaling pathway, leading to the suppression of CCL2 expression and subsequent modulation of monocyte-macrophage migration, thereby establishing a theoretical basis for the effect of MSC-MVs in PF.